[Management of stroke in sub-Saharan Africa: current issues] : Prise en charge des accidents vasculaires cérébraux en Afrique subsaharienne - (:unkn) unknown (My University, 2010)
In sub-Saharan Africa, stroke is likely to present an increasingly important public health problem with a larger relative share of overall morbidity and mortality. Overall, sub-Saharan Health Care is characterized by a lack of human resources, lack of facilities for special investigations, and especially an absence of specific programs addressing the prevention of cardiovascular conditions. Current data on the epidemiology of stroke in sub-Saharan Africa, although sparse and fragmentary, indicate a comparatively high incidence of cerebral hemorrhage associated with high blood pressure, while ischemic stroke in black Africans still appears to be related primarily to small artery disease, HIV infection, and sickle cell disease. With urbanization, the role of large-vessel atherosclerosis is increasing. It is thus essential to coordinate government funding, health care professionals and development agencies to address this rising health problem. Access to health care needs to be better structured, and screening programs should be developed in order to identify and treat vascular risk factors. Improved training of health care professionals is also required in the areas of prevention, diagnosis and management of stroke. Implementation of best-practice recommendations for the management of stroke adapted to the specificities and resources of African countries would help rationalize the scarce resources currently available.
Keywords: African Research